Clean gut : the breakthrough plan for eliminating the root cause of disease and revolutionizing your health - Junger, Alejandro (HarperOne, 2013)
In Clean Gut, Alejandro Junger, M.D, New York Times bestselling author of Clean and creator of the world-famous Clean Program, delivers a complete toolkit for reversing disease and sustaining life-long health.